POTENSI AIR TANAH DAERAH KAMPUS UNDIP TEMBALANG - Widiarso Dian Agus; Pudjihardjo Henarno; Prabowo Wahyu (TEKNIK, 2012)
Provision of clean water in an area need both now and future dating. Provision of clean water can be done byutilizing the potential of existing surface water and ground water. Geoelectric method is widely use forgroundwater investigation. Geoelectric observations at 10 observation points can generate Aquifer Zone Map ofTembalang and surroinding areas.